Clinical and Laboratory Findings of Lead Hepatotoxicity in the Workers of a Car Battery Manufacturing Factory - Bita Dadpour (Iranian Journal of Toxicology, 2016)
Background: Occupational lead poisoning is common in workers of some industries, but lead hepatotoxicity has rarely been reported. Several animal studies have revealed lead induced liver damage but clinical studies concerning the manifestations of lead induced liver toxicity in humans are scares. This study was designed to investigate the clinical manifestations and pathological parameters of hepatic dysfunction and its relationship with blood and urine lead concentrations in a car battery-manufacturing workers. Methods: This cross sectional study was carried out in Mashhad, Iran, during April-June 2011. One hundred and twelve workers underwent blood and urine sampling for determination of lead concentrations and liver function tests. Clinical signs and symptoms of possible lead hepatotoxicity were investigated. Results: Mean (±SD) age of the workers was 28.78 (±5.17) yr with a daytime work of 8.67 (±1.41) h and mean work duration of 3.89 (±2.40) yr. Mean blood lead concentration (BLC) and urine lead concentration (ULC) were 398.95 (±177.41) µg/l and 83.67(±50) μg/l, respectively. We found no correlation between the clinical findings and BLC or ULC. A weak correlation (R: 0.27, P=0.087) between serum alkaline phosphatase concentration and BLC was obtained. No significant relationship was found between other liver function tests and BLC or ULC. Conclusion: We found no specific clinical and laboratory abnormalities of liver in the workers of car battery manufacturer who had chronic lead toxicity. Further investigations with more specific laboratory tests such as LDH5 and gamma glutamyl transferase (GGT) as well as novel biomarkers of metal induced hepatotoxicity might be helpful in evaluating lead hepatotoxicity.